Hospital and Surgeon Adherence to Pediatric Tonsillectomy Guidelines Regarding Perioperative Dexamethasone and Antibiotic Administration. (August 2015) - Padia, Reema; Olsen, Griffin; Henrichsen, Jake; Bullock, Griffin; Gale, Craig; Stoddard, Gregory; Ott, Mark; Srivastava, Rajendu; Meier, Jeremy D.
Objectives: To (1) determine adherence to American Academy of Otolaryngology—Head and Neck Surgery Foundation guidelines for pediatric tonsillectomy recommending routine administration of perioperative dexamethasone and against routine antibiotic administration among surgeons and hospitals in a multihospital network and (2) evaluate the impact of adherence on the risk of complications. Study Design: Case series with chart review. Setting: Multihospital network. Subjects and Methods: A case series of 15, 950 children aged 1 to 18 years undergoing same-day surgery adenotonsillectomy (T&A) within a multihospital network from 2008 to 2014 was reviewed to determine whether dexamethasone and/or antibiotics were given in the hospital. The frequency of dexamethasone and antibiotic administration was compared among surgeons and hospitals in the years before and after the guidelines were published. The frequency of complications was compared in adhering vs nonadhering surgeons. Results: The study cohort included 15, 950 children undergoing T&A at 19 hospitals by 74 surgeons. Of the patients before guideline publication, 98.4% (n = 7432) received dexamethasone compared with 98.9% of subjects after guideline publication (n = 8518). In total, 16.1% received antibiotics before the guidelines compared with 13.8% after. Prior to the guidelines, 27 of 74 surgeons (36%) routinely gave antibiotics. After the guidelines were published, 19 surgeons (26%) continued to give antibiotics more than 50% of the time. There was no difference in complication visits between adhering and nonadhering surgeons. Conclusions: Most hospitals and surgeons administered perioperative dexamethasone routinely. While the overall frequency of antibiotic administration decreased after the guidelines were published, a significant percentage of surgeons continued to give antibiotics routinely, suggesting the need for improved dissemination and implementation of guidelines to promote adherence.